Evaluation of industrial work practice program in Vocational High School 1 Rejotangan - Andini Dwi Rachmawati; Yaya Sukjaya Kusumah (Jurnal Pendidikan Vokasi, 2023)
This study aims to evaluate implementing the Industrial Work Practice (Prakerin) program at the Vocational High School (VHS) of 1 Rejotangan. This type of research is evaluative with a descriptive qualitative method using the CIPP model. The population of this study was 15 students involved, five work of world instructors, 21 teacher councils, and the headmaster of VHS of 1 Rejotangan. Data collection techniques use interviews and observations. Interviews are conducted openly and behind closed doors. The interview was conducted with the headmaster of VHS of 1 Rejotangan. The observations made by the researchers aimed to capture data on pre-employment activities, sincerity, and cooperation of participants and instructors during the activity. The results of this study are (1) synchronization of the joint curriculum to the world of work at the evaluation stage of the context of the VKS of 1 Rejotangan industrial practice program. At this stage, (1) the signing of an MOU between the world of work schools, a student readiness plan (competency mapping), and a placement plan (world of work Placement Mapping); (2) input evaluation obtained information that a cooperative organization was formed. The cooperative organization between schools and the business world and industry in the industrial practice program has two aspects: departmentalization and division of labor. The division of labor comprises principals and teachers from the business/industrial world. Meanwhile, departmentalization consists of mapping students. Place students in existing competencies and an appropriate world of work; (3) process evaluation, a collaboration between schools and the world of work for student development, is flexible and consistent with each school's policies; (4) product evaluation. The internship program has many benefits for schools and the world of work.